2022
DOI: 10.1016/j.jbc.2021.101464
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the molecular basis of substrate recognition by the wall teichoic acid glycosyltransferase TagA

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
(193 reference statements)
0
2
0
Order By: Relevance
“…Similar results were reported for B. subtilis TagA, a teichoic acid glycosyltransferase. TagA binds both UDP- N -acetylmannosamine (UDP-ManNAc) and UDP-GlcNAc but is enzymatically active only with UDP-ManNAc [30]. This finding raises the question of how the efficiency of WTA rhamnosylation is ensured in bacteria since other TDP coupled sugars will compete for the TDP-rhamnose binding site, slowing the production of decorated WTA.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported for B. subtilis TagA, a teichoic acid glycosyltransferase. TagA binds both UDP- N -acetylmannosamine (UDP-ManNAc) and UDP-GlcNAc but is enzymatically active only with UDP-ManNAc [30]. This finding raises the question of how the efficiency of WTA rhamnosylation is ensured in bacteria since other TDP coupled sugars will compete for the TDP-rhamnose binding site, slowing the production of decorated WTA.…”
Section: Discussionmentioning
confidence: 99%
“…tagA-deficient strains are less toxic and sensitive to methicillin, imipenem, and ceftazidime (D'Elia et al, 2006a,b;Farha et al, 2015). Moreover, it has found that five residues (E210, W211, R214, R221, and R224) of the C-terminal in TagA are crucial to its catalysis (Martinez et al, 2022), suggesting the discovery of new antibiotics that could be achieved by disrupting the synthesis of important polymers. Similarly, the serine active sites of TagB and TagC were also discovered, which play an important role in bacterial adhesion, aggregation, invasion, and infection (Pokharel et al, 2020).…”
Section: Teichoic Acidmentioning
confidence: 99%